Detecting Schizophrenia: Low vs High Dimensional Brain Imaging Features - Ayman Alfahid (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Early detection of schizophrenia is critical to minimize its long-term effects. This study investigates the impact of low-dimensional (Regions of Interest) and high-dimensional features (Voxel-based morphometry) on models’ predictive performance for schizophrenia detection. Using the brain imaging data provided by RAMP, the study investigates the performance of a regularized linear, ensemble, and non-linear models combined with different cross-validation strategies on the low- and high-dimensional feature sets. The results show that the regularized linear model consistently outperforms the ensemble and non-linear models across both feature sets in terms of ROC-AUC, balanced accuracy, and computational efficiency. Our study also reveals that the choice of feature dimensionality does indeed impact schizophrenia detection as the low-dimensional features outperform high-dimensional features across all metrics and models. This suggests that the Regions of Interests, despite their reduced dimensionality and complexity, contain sufficient discriminative information for identifying schizophrenia, whereas the additional detail provided by the Voxel-based morphometry features does not necessarily enhance model performance. Overall, regularized linear model, combined with low-dimensional features and standard cross-validation, offers the most promising results. Using an interpretability tool, we obtained the features that have the most impact on schizophrenia detection with right pallidum grey matter volume being the most influential factor.